AUDIT INVESTIGATION OF JOINT STOCK COMPANIES - Tulovov Erkinjon Tolqin oglu (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
One of the main conditions for any joint-stock company to operate in the market is strict adherence to accounting and financial discipline. Joint-stock companies must undergo an annual audit in accordance with Article 10 of the Law of the Republic of Uzbekistan on Auditing. All settlements for the sale of goods and services must be completed within the timeframe set by the agreement approved by both parties. The breach of obligations has led to non-fulfillment of production plans by businesses, as well as an increase in accounts payable and the deterioration of their financial condition.